EXPLORING CHALLENGES IN IRAN'S KNOWLEDGE-BASED ICT FIRMS: IMPLICATIONS FOR EDUCATIONAL TECHNOLOGIES - Fotoohi, Arezoo (DeReMa (Development Research of Management): Jurnal Manajemen, 2024)
This study explores the multifaceted growth challenges faced by Knowledge-Based Firms (KBFs) within Iran’s Information and Communication Technology (ICT) sector. The research identifies critical barriers across several domains, including financial constraints, market development limitations, and political, regulatory, and legal complexities. Through a comprehensive analysis, the study reveals that financial challenges are intensified by limited access to high-quality equipment and skilled personnel. Additionally, both domestic and international market development face significant hurdles. Regulatory and legal issues, such as inadequate intellectual property protections and cumbersome administrative processes, further exacerbate these challenges. The study underscores the need for strategic policy reforms, improved governmental coordination, and targeted support mechanisms to address the evolving needs of these firms. The findings highlight the importance of optimizing tax policies, facilitating international market entry, revising regulatory frameworks, and enhancing support for knowledge-based law enforcement to foster sustainable growth and innovation in Iran’s ICT sector.Abstrak dalam Bahasa Indonesia. Penelitian ini mengeksplorasi tantangan pertumbuhan yang kompleks yang dihadapi oleh Perusahaan Berbasis Pengetahuan (KBFs) dalam sektor Teknologi Informasi dan Komunikasi (ICT) di Iran. Penelitian ini mengidentifikasi hambatan kritis di berbagai bidang, termasuk keterbatasan keuangan, keterbatasan pengembangan pasar, serta kompleksitas politik, regulasi, dan hukum. Melalui analisis yang komprehensif, penelitian ini mengungkapkan bahwa tantangan keuangan diperparah oleh terbatasnya akses terhadap peralatan berkualitas tinggi dan tenaga kerja terampil. Selain itu, pengembangan pasar domestik dan internasional menghadapi hambatan yang signifikan. Masalah regulasi dan hukum, seperti perlindungan hak kekayaan intelektual yang tidak memadai dan proses administratif yang rumit, semakin memperburuk tantangan ini. Penelitian ini menekankan perlunya reformasi kebijakan strategis, peningkatan koordinasi pemerintah, dan mekanisme dukungan yang tepat untuk mengatasi kebutuhan yang berkembang dari perusahaan-perusahaan ini. Temuan ini menyoroti pentingnya mengoptimalkan kebijakan pajak, memfasilitasi masuknya pasar internasional, merevisi kerangka regulasi, dan meningkatkan dukungan untuk penegakan hukum berbasis pengetahuan guna mendorong pertumbuhan yang berkelanjutan dan inovasi dalam sektor ICT di Iran